Distribution and persistence of fecal coliform (Escherichia coli) in water and sediment of semariang batu river, Kuching, Sarawak - Magarate Rita, Elvis Sulang (Universiti Malaysia Sarawak (UNIMAS), 2010)
Escherichia coli (E. coli) is an indicator organisms used worldwide to assess microbiological safety in drinking water, recreational waters and fresh water. In this study, E. coli was isolated from water and sediment samples of four locations of Semariang Batu River, Kuching, which were Lemidin River (S1), Semariang Batu River (S2), Loba Kara River (S3) and Batang Mangkuang River (S4). All of the sampling stations had different activities which were construction area (S1), residential area (S2), shrimp farm (S3) and area of no obvious human activities (S4). In order to perform the survival study, E. coli was isolated, grown and inoculated in the sediment samples. E. coli was incubated under 25°C and 30°C and the population was observed until undetechable. Besides, pipette method was conducted to find the particle size of the sediment and loss-on-ignition method was performed for organic matter content. Results showed that S3 has the highest counts of fecal coliform (E. coli) in water sample (>1100 MPN/100ml), while S2 has the highest counts in sediment sample (12659.22 MPN/100g dry weight). It was found that there was significant difference between mean population and sampling stations in both water and sediment samples. At 25°C and 30°C there was significant difference of mean population in day two. E. coli in sediment from S4 survived longer due to high clay content. Further studies need to be conducted to determine the E. coli strain and other pathogenic organism’s presence in the Semariang Batu River.